2017
DOI: 10.21873/anticanres.11332
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictive Role of MicroRNAs in the Neoadjuvant Treatment of Esophageal Cancer

Abstract: Esophageal cancer is a disease with disappointing prognosis. Currently, there are no predictive factors that can identify patients who on the one hand would likely benefit from tri-modality management and, on the other hand, would not be significantly affected by the morbidity accompanying the treatment. MicroRNAs are short non-coding RNAs responsible for post-transcriptional modification of gene expression by binding to 3'-UTR of messenger RNA and represent emerging potential predictive biomarkers of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…36 At the molecular biology level, the genetic susceptibility of esophageal cancer is related to the activation and expression of oncogenes and the loss or inactivation of tumor suppressor genes. 19,33 At present, the specific pathogenesis of esophageal cancer is still unclear. Molecular biology research on esophageal cancer, searching for early diagnostic markers of esophageal cancer and related factors and mechanisms of invasion and metastasis have become a hot topic in this field.…”
Section: Discussionmentioning
confidence: 99%
“…36 At the molecular biology level, the genetic susceptibility of esophageal cancer is related to the activation and expression of oncogenes and the loss or inactivation of tumor suppressor genes. 19,33 At present, the specific pathogenesis of esophageal cancer is still unclear. Molecular biology research on esophageal cancer, searching for early diagnostic markers of esophageal cancer and related factors and mechanisms of invasion and metastasis have become a hot topic in this field.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been recognized as a new class of genes involved in human cancer and have recently been shown to be biomarkers of diagnostic, prognostic and therapeutic (10,11). Several studies have identified some miRNAs that were significantly altered and have the potential to restrain proliferation of cervical cancer (12,13). Previous studies suggest that miRNA-138 restrains cervical cancer cells proliferation (14).…”
Section: Introductionmentioning
confidence: 99%
“…Paralysis of the left reccurent laryngeal nerve in patients operated on using the cervical approach is reported in up to 14% of patients 35 . There is a consensus that is based on the analysis of postoperative results that surgery for esophageal cancer should be performed in high volume centres 36, however despite this effort and intensive research in this field [37][38][39] the general outcome of the treatment remains unsatisfactory. The present retrospective analysis has some obvious limitations.…”
Section: Discussionmentioning
confidence: 99%